2003
DOI: 10.1086/379072
|View full text |Cite
|
Sign up to set email alerts
|

Difficulty Swallowing and Lack of Receipt of Highly Active Antiretroviral Therapy Predict Acute Weight Loss in Human Immunodeficiency Virus Disease

Abstract: In human immunodeficiency virus (HIV) disease, symptoms of underlying illness may promote weight loss through decreased caloric intake, increased metabolic needs, or nutrient malabsorption. We evaluated disease symptoms as predictors of acute weight loss (i.e., loss of > or =5% of weight). HIV-infected men and women (n=415) were telephoned every 5 weeks to obtain information about weight and recent symptoms. Weight change between each pair of consecutive calls (telephone intervals, 2814) was calculated. Acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…with the findings of studies that were conducted in England (15) and in the United States (16,41), we found that events that interfere with nutrient intake (ie, oral ulcers, thrush, and vomiting) or absorption (ie, diarrhea) were significant risk factors for wasting when measured as a first episode of a low MUAC or BMI. In addition, we found that episodes of weight loss were more frequently accompanied by morbidity events than were episodes with no weight loss.…”
Section: Discussionsupporting
confidence: 67%
“…with the findings of studies that were conducted in England (15) and in the United States (16,41), we found that events that interfere with nutrient intake (ie, oral ulcers, thrush, and vomiting) or absorption (ie, diarrhea) were significant risk factors for wasting when measured as a first episode of a low MUAC or BMI. In addition, we found that episodes of weight loss were more frequently accompanied by morbidity events than were episodes with no weight loss.…”
Section: Discussionsupporting
confidence: 67%
“…In one study, about a third of the patients treated with HAART had weight loss, as is in our patients, and it remained the most important prognostic marker [ 24 ]. Poor nutritional intake, metabolic disturbances because of drugs, and infectious conditions such as tuberculosis could be possible contributing reasons [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The severity of weight loss has diminished compared with the pre-HAART era, but the incidence of weight loss has not [1][2][3] . The causes of persisting weight loss and malnutrition in HIV-infected individuals are multifactorial, with decreased energy intake due to anorexia and nausea related to HIV-associated illness or medications, increased energy demands related to chronic infection, HAART use, trouble swallowing/other oral problems and malabsorption/other gastrointestinal disorders all playing a role [4][5][6][7][8][9] .…”
mentioning
confidence: 99%